Tone and vowel perception delay: long-term effects of late cochlear implant in children with prelingual deafness - Liang, Maojin; Peng, Peng; Liu, Jiahao; Wang, Zhengye; Lai, Kaiying; Wang, Junbo; Zheng, Yiqing; Wang, Suiping (Frontiers in Human Neuroscience, 2025)
PurposeThe influence of the duration of the subsequent rehabilitation period on the perception of Mandarin tones and vowels has not been fully investigated. This study explores phoneme perception and event-related potential (ERP) responses in prelingually cochlear implant (CI) children, comparing early (eCI) vs. late implantation (lCI) with 5-year rehabilitation.Method and resultsThis study involved 19 early cochlear implanted (eCI) children, 19 late cochlear implanted (lCI) children (both right-ear implantation), and 21 normal-hearing (NH) children as a control group. EEG data were recorded for all groups during a passive multi-feature auditory oddball paradigm, involving deviant and standard stimuli. Behavioral performance was also assessed to validate Electroencephalogram-based (EEG-based) indicators. Results showed that the lCI group had significantly longer P2 latency and amplitude in the ERP test compared to the NH group, but not the eCI group. Both CI groups had smaller mismatch negativity (MMN) amplitudes than the NH group in tone and consonant conditions. The lCI group showed larger late discriminative negativity (LDN) amplitudes than the eCI group in tone and vowel conditions. Behavioral results aligned with EEG findings, with the eCI group performing better than the lCI group in tone and vowel conditions. The LDN amplitude in CI groups is larger for both tone and vowel conditions when the age at cochlear implantation is older.ConclusionThese results indicate that (1) the earlier the age of implantation, the better the ability to perceive tones; (2) Implantation age of CI showed no significant effect on consonant perception; (3) The LDN component may be an indicator to discriminate eCI and lCI children in terms of Mandarin tone and vowel perception. (4) The P2 latency and amplitude may be an indicator to discriminate NH and CI children in phoneme perception.